The coastal aquifer recovery subject to storm surge: Effects of connected heterogeneity, physical barrier and surge frequency - Song, Jian; Yang, Yun; Wu, Jianfeng; Wu, Jichun (Journal of hydrology (Amsterdam), 2022)
•Connected aquifer has the greater salinized extent and shorter recovery time.•Physical barrier prolongs the recovery time as connectivity level elevates.•High-frequency surge increases residual salinized volume and salt mass.•Vertical intrusion distance is a key indicator for the risk assessment of surges. Storm surge, a worldwide phenomenon triggering the vertical saltwater infiltration, is likely to exacerbate coastal groundwater salinization due to geologic heterogeneity, anthropogenic engineering and climate change. This study analyzed the combined effects of connected heterogeneity, physical barrier and surge frequency on the coastal aquifer recovery. A series of modeling cases were investigated using HydroGeoSphere in the heterogeneous and equivalent homogeneous aquifer. The heterogeneity setting is composed of different connectivity level of hydraulic conductivity field. The simulation results of single storm surge event demonstrate that the connected heterogeneity elevates the salinized extent and reduces the aquifer recovery time due to a number of preferential flow paths. In comparison to the equivalent homogeneous aquifer, heterogeneity alleviates the maximum salinized extent and vertical intrusion distance due to the accelerated mixing of salinized groundwater with fresh groundwater. Physical barrier, classified as subsurface dam and cutoff wall, leading to different groundwater discharge pattern is tailored to investigate the influences of the permanent subsurface engineering on the aquifer recovery. Our results show that the connectivity level controls the salinization pattern subject to physical barrier. Then, the repetitive storm surge events were simulated to investigate the effects of surge frequency. For the low-frequency surge event, the variation of salinized metric is the repetition of the unimodal curve in the single surge event. Nevertheless, for the high-frequency surge event, the residual salt mass cannot be flushed out over the simulation period, especially for the low-connectivity aquifer. Meanwhile, the high-frequency surge event broadens the differences of aquifer recovery process due to physical barrier. These findings have critical implications for coastal groundwater management which is facing the substantial environmental risks of surge-induced vertical saltwater intrusion derived from geologic heterogeneity and climate changes.